IMPROVING THE STUDENTS’ WRITING ABILITY THROUGH PICTURE SERIES FOR DEAF AND HARD OF HEARING LEARNERS - Euis Setiati; Resty Wirianty Gemilang (IKIP Siliwangi, 2019)
This research is classroom action research that was done in two cycles. The data was gathered through test, observation and interview. This research was conducted in SMPLB-B Prima Bhakti Mulia at Cimahi Utara. The respondents of this research was the eitht grade students. Furthermore, the data from observation and interview showed that there are some benefits, those are the increasing of students’ participation in the class, increasing of students’ writing interest and fun learning’s atmosphere. With the used of pictures series make easily understand and write the descriptive text for the deaf and hard to hearing learners. The findings showed that In Cycle 1, there were 5 students (74%) of 7 students who achieved the minimum passing grade and the remaining 2 students (26%) who had not achieved, the highest score research is 80 and the lowest score achievement is 55. This cycle is not successful because it does not reach the success criteria. In Cycle 2, there were 6 students (82%) who achieved minimum passing grade and there were 1 students (18%) of the students who did not pass the minimum passing grade, the highest achievement score in this cycle is 90 and the lowest achievement score is 60. This indicates that picture series had significance improve on students’ writing ability for deaf and hard of hearing learners.